The work capability assessment and a "real world" test of incapacity: Considerations from, and for, quantitative research - Richard Berthoud (University of Essex, Institute for Social and Economic Research (ISER), 2011)
The Work Capability Assessment governs entitlement to the Employment and Support Allowance - the social security benefit for people who are incapable of work. It is based on rules which decide entitlement according to the combination of impairments experienced by the claimant. This paper discusses the relative merits of formal regulations and discretionary judgements in the assessment of incapacity, and considers the possible introduction of a discretionary (real world) test to complement the current rigid scoring system. The paper concludes with suggestions for further research which would shed light on the processes by which claimants are judged incapable of work.
Keywords: I38; J14; J64; 330; disability; incapacity; social security; adjudication; Arbeitsmarkt; Behinderte Arbeitskräfte; Soziale Sicherung; Theorie